Day 1 Wed, April 05, 2017 2017
DOI: 10.2118/185937-ms
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Fluid Properties Using Surrogate Models and Fluid Database

Abstract: Laboratory experiment is the main tool for determining fluid properties such as saturation pressure, formation volume factor, fluid density and viscosity. However, both sampling and experiments are limited by cost and time. On the other hand, the information about the fluid properties are essential for reservoir engineering works such as reserves and productivity calculation. Therefore, empirical correlations are commonly used as an alternative method. Researchers developed empirical correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…A rise in pressure induces an increment in both the viscosity and density, whereas an increase in gas content induces a decline in viscosity and density. The results corresponds to the findings of Arief et al 14 , that the prediction performance of Kriging exceeds the discussed correlations from literature. The authors reported an estimation error of 20.7 MARE%, while this study presents a higher accuracy by implementing the saturated density.…”
Section: Rbfnsupporting
confidence: 90%
See 2 more Smart Citations
“…A rise in pressure induces an increment in both the viscosity and density, whereas an increase in gas content induces a decline in viscosity and density. The results corresponds to the findings of Arief et al 14 , that the prediction performance of Kriging exceeds the discussed correlations from literature. The authors reported an estimation error of 20.7 MARE%, while this study presents a higher accuracy by implementing the saturated density.…”
Section: Rbfnsupporting
confidence: 90%
“…only the input and output variables have any influence to the model 13 . The aim of the surrogate model is to replace time consuming and cumbersome simulations and experiments to predict the outcome variables of a known input set 14 .…”
Section: Surrogate Modelsmentioning
confidence: 99%
See 1 more Smart Citation